2018
DOI: 10.1016/j.apergo.2018.03.009
|View full text |Cite
|
Sign up to set email alerts
|

Learning flight procedures by enacting and receiving feedback

Abstract: Learning flight procedures is part of any pilot training. The conventional learning method consists in learning and practicing the procedure written on a sheet of paper along with printed images of the cockpit. The purpose of the present paper was to test the efficiency of a tactile interactive multimedia training tool designed to foster the self-regulated learning of flight procedures, especially through enacting relevant gestures and providing feedback. Results showed that learning with this tool did not lea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…A priority for the aviation industry is training flightcrews on procedures, with an emphasis on those pertaining to corrective actions in response to non-routine and emergency situations on the flight deck (Human Factors & Aviation Safety, 2019). Training of procedures requires both the conveying of knowledge (declarative and procedural) and the practice of skills (Matton et al, 2018), and it is traditionally provided through either live training or high-fidelity simulation (Dunne et al, 2010). However, organizations increasingly use E&DL to satisfy learning needs (Martins, 2019), and this shift has only accelerated recently.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A priority for the aviation industry is training flightcrews on procedures, with an emphasis on those pertaining to corrective actions in response to non-routine and emergency situations on the flight deck (Human Factors & Aviation Safety, 2019). Training of procedures requires both the conveying of knowledge (declarative and procedural) and the practice of skills (Matton et al, 2018), and it is traditionally provided through either live training or high-fidelity simulation (Dunne et al, 2010). However, organizations increasingly use E&DL to satisfy learning needs (Martins, 2019), and this shift has only accelerated recently.…”
Section: Discussionmentioning
confidence: 99%
“…In a meta-analysis, Kaplan et al (2020) found that Extended Reality (XR) platforms are more suitable for training physical tasks but are otherwise equally effective to traditional approaches. There is also some evidence that incorporating other modalities, specifically, emphasis on haptic interfaces, may improve the efficacy of VR training (Sigrist et al, 2013;Matton et al, 2018). AR has so far been limited to individual cases studies in the literature, but these have demonstrated that AR can be an effective medium for training knowledge, procedures, and spatial tasks (Hatfield et al, 2019).…”
Section: Scenario-based Training (Sbt)mentioning
confidence: 99%